1)(5b+6)(5b-6) 2)(5c+2a)(5c-2a) 3)(3x-y)(3x+y) 4)(4a-b)(b-4a)

варвара563536536 варвара563536536    1   16.09.2019 16:20    0

Ответы
RomeOMeD RomeOMeD  07.10.2020 20:04
1) (a + b) × (a - b) = a² - b²,
(5b + 6) × (5b - 6) = 5b² - 6² = 5b² - 6² = 5b² - 36 = 25b² - 36.
2) (a + b) × (a - b) = a² - b²,
(5c + 2a) × (5c - 2a) = 5c² - 2a² = 25c² - 4a².
3) (a + b) × (a - b) = a² - b²,
(3x - y) × (3x + y) = 3x² - y² = 9x² - y².
4) (a + b) × (a - b) = a² - b²,
(4a - b) × (b - 4a) = 4a² - b² = 16a² - b².
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра